Therapeutic Drug Monitoring of Zuclopenthixol in a Double-Blind Placebo-Controlled Discontinuation Study in Adults with Intellectual Disabilities and Aggressive Behaviour - Schwarz, V.; Reis, O.; Glaser, T.; Thome, J.; Hiemke, C.; Haessler, F. (Pharmacopsychiatry, 2014)
The trial was a double-blind, placebo-controlled comparison with a discontinuation design. 49 mentally retarded patients with aggressive behaviour were treated with zuclopenthixol at a dose of 2–20 mg/d. At each visit the clinical effect was evaluated. Correlations between dose, serum concentration, and efficacy measures were calculated. The mean dose was 10.0 mg/day (±5.17); the mean serum concentration 4.19 ng/mL (±3.16). Associations of dosage, serum concentration and clinical efficiency did not result in coherent patterns. Correlations with clinical efficiency measures appeared to be contradictory for dosage and serum concentrations, respectively. As no consistent associations between dosage, serum concentration, and clinical efficiency measures were found, different hypotheses explaining the results are discussed.
Keywords: mental retardation; aggression treatment; antipsychotic drugs; drug monitoring; zuclopenthixol